Sweet potatoes for profit - Kyle, E. J. (Edwin Jackson), 1876- (Bulletin (Agricultural and Mechanical College of Texas. Extension Service), 1915)
"Simple directions for banking and storing sweet potatoes to prevent loss in marketing."